A construção discursiva sobre o conceito de desenvolvimento sustentável - SIQUEIRA, Ivone dos Santos (Universidade Federal do Pará, 2020)
This article presents discourses related to the Sustainable Development concept starting from the Environmental Crisis, the historical milestone related to the concept in question, as well as explaining and discussing theses and dissertations that deal with the concept of sustainable development based on analysis of discourses that include representations e interpretations that are made discourses published by the journalistic media having as reference the publications of scientific journals, theses and dissertations, that comprise the period from 2010 to 2019. Data analysis generated two categories: discourses on Sustainable Development from the perspective of economic development presente in the media and the discourses of sustainable development in the exploitation of natural resources. The discourses presented link the concept of economic development to the capitalist logic of economic development.